1984
DOI: 10.1302/0301-620x.66b1.6693477
|View full text |Cite
|
Sign up to set email alerts
|

The long-term results of Stanmore total knee replacements

Abstract: One hundred and three sequential Stanmore knee replacements were reviewed retrospectively on two occasions with a maximal follow-up period of nine years three months. This knee prosthesis, which is hinged, was successful In alleviating pain, stabilisIng an unstable knee and modestly IncreasIng the arc of flexion. Walking capacity was increased and flexion contractures were reduced. There were seven cases of Infection and four of fracture around the prosthesis. All these proved difficult to freat and two knees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
5

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 9 publications
0
10
0
5
Order By: Relevance
“…24 The technique of survivorship analysis was applied only in the 1980s and there are few such analyses involving hinged prostheses. Most of the older designs of hinged prostheses yielded unacceptably poor results, 25,26 but those of the second-generation St Georg and the Blauth prosthesis are equal to, or better than, the best outcomes of resurfacing prostheses. We were able to examine the condylar surface, the polyethylene menisci and the polyethylene bush of a Blauth prosthesis which had been revised 150 months after insertion because of aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…24 The technique of survivorship analysis was applied only in the 1980s and there are few such analyses involving hinged prostheses. Most of the older designs of hinged prostheses yielded unacceptably poor results, 25,26 but those of the second-generation St Georg and the Blauth prosthesis are equal to, or better than, the best outcomes of resurfacing prostheses. We were able to examine the condylar surface, the polyethylene menisci and the polyethylene bush of a Blauth prosthesis which had been revised 150 months after insertion because of aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…26 The endoprostheses which we have used were initially based on the Stanmore hinged knee, the long-term results of which were not encouraging, with failure rates between 20% and 30% at eight years. 27,28 After resection of a tumour around the knee, all knee ligaments are removed and there may well be considerable muscle loss. Any endoprosthesis must replace the length of bone missing, provide a stable knee and allow sufficient hyperextension for the knee to 'lock'.…”
Section: Discussionmentioning
confidence: 99%
“…In conventional knee replacements for osteoarthritis these implants have been shown to have a very high failure rate and are not recommended for routine use. 20 Unwin et al 16 found that the failure rate for aseptic loosening alone in their large series of endoprostheses around the knee was 50% at 20 years which is a failure rate of 2.5% per year. This does not include other causes such as infection and implant failure which are responsible for an extra failure rate of 1.5% per annum.…”
Section: Figmentioning
confidence: 99%